Gene structure, expression and regulation: translation and regulation of gene expression - Sargent, Carole (Henry Stewart Talks, 2020)
The translation process, The ribosome and ribosomal RNA, Loading tRNA with amino acid, Translation initiation, Translation elongation, Translation termination, Post translation modification, Diverse mechanisms to control of gene expression, Promoter usage determines protein product, The roles of non-coding RNAs, Chromatin level modifications